A taxonomic account on the phytoplankton of a pond receiving textile industrial effluents - Begum, Z.N. Tahmida (Bangladesh Journal of Plant Taxonomy, 2008)
Phytoplankton from four stations of a large pond receiving effluents from two textile industries have been investigated. A total of 69 taxa were identified out of which 48 belonged to Chlorophyceae followed by 17 to Cyanophyceae. One species from each of Chrysophyceae, Xanthophyceae, Cryptophyceae and Dinophyceae were also recorded. Oscillatoria limnetica Lemm., Anabaena circinalis Rabenh. ex Born. et Flah., Nostoc commune Vaucher ex Born. et Flah. Ankistrodesmus falcatus var. mirabilis (West & West) Lemm. and Scendesmus spp. were found dominant in all the stations. Keywords: Industrial effluents, Phytoplankton, Taxonomy Â  DOI: 10.3329/bjpt.v15i2.1742 Â  Bangladesh J. Plant Taxon. 15(2): 129-139, 2008 (December)